Evaluation of less treatment interruption of 6-Mercaptopurine by co-administration of ursodeoxycholic acid with chemotherapy in pediatric acute lymphoblastic leukemia - Yesmin, Nafisa; Karim, M. Anwarul; Mazid, Abu Haider Mohammad Raziul; Mahmud, Niaz (International Journal of Contemporary Pediatrics, 2024)
Background: Ursodeoxycholic acid (UDCA), a bile acid, protects the liver through various mechanisms, including bile composition modulation and enhanced secretion. In ALL chemotherapy, 6MP is hepatotoxic, requiring dose reduction. UDCA is used to alleviate liver toxicity in ALL and other chronic cholestatic conditions. The study aims to evaluate the effectiveness of UDCA with chemotherapy in reducing 6MP treatment interruptions and its impact on treatment continuity in pediatric ALL. Methods: This randomized controlled trial study conducted at the Department of Pediatric Hematology and Oncology, BSMMU in pediatric ALL patients during chemotherapy from September 2018 to August 2019. Fifty children aged 1 to 18 years with ALL were enrolled, half receiving UDCA alongside chemotherapy and the rest forming the control group. Serum hepatic transaminases, total bilirubin, and CBC were monitored every 14 days. Statistical analysis was performed using SPSS, with significance set at p<0.05. Results: In this study of 50 pediatric ALL patients, there were no statistically significant age or gender differences between the "Case" (UDCA-treated) and "Control" groups. However, the UDCA group showed a significant decrease in abnormal liver function tests (32.0%) compared to controls (60.0%). Moreover, 6MP dose reduction was significantly lower in cases (4.0%) than controls (40.0%), indicating UDCA’s potential hepatoprotective effects. Multivariate logistic regression revealed male gender and mean AST levels as significant factors associated with hepatotoxicity in pediatric ALL patients. Conclusions: Co-administration of UDCA with chemotherapy demonstrates a significant effect in treatment interruption by hepatotoxic drug specially 6 MP in pediatric ALL patients.